Eimeria vermiformis infection reduces goblet cells by multiplication in the crypt cells of the small intestine of C57BL/6 mice - Linh, Bui Khanh; Hayashi, Toshiharu; Horii, Yoichiro (Parasitology research (1987), 2009)
In the gastrointestinal mucosa, mucus produced by goblet cells plays an important role in the defense against various pathogens. It is well known that some helminth parasites are able to up-regulate goblet cell numbers and alter the mucus components. However, the nature of the interactions between the protozoan parasites and goblet cells is still unclear. To clarify this point, we examined the goblet cell response in the small intestinal epithelium in C57BL/6 mice with Eimeria vermiformis infection. On day 6 post-infection (p.i.), we observed E. vermiformis multiplication followed by their destruction within the epithelium of the crypt. However, this was not observed in the villi. There was no evidence that the parasite destroyed the goblet cells; moreover, the number of goblet cells decreased in association with the development of the endogenous stages of E. vermiformis in the jejunum and ileum, but not in the duodenum. During this time, we observed infiltration into the lamina propria by lymphoid cells, such as plasma cells and lymphocytes with some eosinophils, in addition to villous atrophy. A significant reduction of goblet cell numbers occurred on days 8 and 10 p.i. Starting from day 12 p.i., elimination/termination of E. vermiformis was noted, and there was recovery of the villous epithelium along with regeneration of the crypt and goblet cells. The current study examined the reduction of goblet cells and their possible importance in eimerian infections.